2014
DOI: 10.1111/jphp.12347
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal and intravenous administration of octa-arginine modified poly(lactic-co-glycolic acid) nanoparticles facilitates central nervous system delivery of loperamide

Abstract: This study demonstrates the potential of R8-PLGA NPs as carriers of therapeutic agents to the CNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
(71 reference statements)
1
15
0
Order By: Relevance
“…The present results on the penetration of functionalized NPs in the cortical parenchyma are supported by previous reports on the presence of apoE‐functionalized albumin NPs (250 nm in size) in cortical neurons 30 min after iv injection in mice and rats . Uptake of PLGA NPs functionalized with peptides (glycopeptide, leptin‐derived peptide, and phage‐displayed peptide), but not non‐functionalized ones, by cortical neurons was also shown in rats at 2 h after systemic injection …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present results on the penetration of functionalized NPs in the cortical parenchyma are supported by previous reports on the presence of apoE‐functionalized albumin NPs (250 nm in size) in cortical neurons 30 min after iv injection in mice and rats . Uptake of PLGA NPs functionalized with peptides (glycopeptide, leptin‐derived peptide, and phage‐displayed peptide), but not non‐functionalized ones, by cortical neurons was also shown in rats at 2 h after systemic injection …”
Section: Discussionsupporting
confidence: 91%
“…Concerning the size of the custom‐made, non‐functionalized PLGA NPs, previous studies indicated that NPs in a similar dimensional range can provide tools for drug delivery to the brain . However, NP size is a critical parameter for BBB traversal, and in the present study non‐functionalized PLGA NPs were not found to enter the brain parenchyma.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The main strategy to improve drug delivery to the brain by intranasal administration is the modification of nanoparticles by absorption and permeation enhancers. For that purpose, surfactants, bile salts, cyclodextrins, derivatives of chitosan, arginine, lactoferrin, have already been proposed [11][12][13][14][15][16]. Liposomes are well-known universal nano-carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, PLGA is approved by the US Food and Drug Administration and the European Medicine Agency in various drug delivery systems, including polymeric NPs in human [19]. Furthermore, studies[20,21] have shown the potential of PLGA‐NPs as carriers of therapeutic agents to the brain.…”
Section: Introductionmentioning
confidence: 99%